PRE-SCHOOL EDUCATION ESTABLISHMENT AS A SYSTEM INSTITUTION FOR THE FORMATION OF HEALTH CARE COMPETENCES OF A CHILD - Denisyak, Julia (Mountain School of Ukrainian Carpaty, 2022)
The article analyzes and substantiates the essence and role of the preschool education institution as the first systematic educational institution where the process of forming the health-preserving competence of a preschool child takes place. The difficult circumstances in life of the Ukrainian state nowadays (i.e. a long lockdown and a war) proved the importance and necessity of the functioning of kindergartens as the first systematic, methodically grounded and highly capable institution where the formation of a preschool child takes place. In such circumstances, it is necessary to focus attention on the child's development, as one of those factors that make it possible to abstract and relieve oneself in the extremely difficult conditions of wartime, active hostilities, life's uncertainty, fear and hopelessness. We see the development of a preschool child as important in such aspects as: development of the ability to adapt to certain adverse circumstances; to adapt to new living conditions; communicate with new people of different ages; develop creative abilities and form new creative skills; use all available opportunities, means and factors to create an atmosphere of peace, relaxation, rest or creative tension, etc. In the article, we prove that pedagogical facilitation is important for the integral formation of a child's healthpreserving competence in a preschool education establishment. Teaching the future teachers the basics of "happiness pedagogy" and the methods of forming the child's health-preserving competence in a preschool education establishment is a component of their professional competence and suitability. Modern educational programs for training teachers to work with preschool children should contain means and methods for developing these competencies of teachers. Keywords: health care competence, child, preschool, development, teacher, pedagogical facilitation, preschool education establishment.